2020
DOI: 10.1188/20.onf.318-330
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Exploration of Prostate Cancer Survivors Experiencing Psychological Distress: Loss of Self, Function, Connection, and Control

Abstract: Purpose: To explore the experiences of men with prostate cancer identified as having psychological distress and to identify factors influencing distress. Participants and setting: 28 men with prostate cancer diagnosed 18-42 months earlier, identified as having psychological distress on survey measures. Methodologic approach: Semi-structured telephone interviews were conducted. Thematic analysis using a Framework approach was used. Findings: Men with psychological distress had strong perceptions of 'loss' towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 62 publications
1
13
0
3
Order By: Relevance
“…Retaining sexual function was also so important to some men that they recounted choosing treatment depending on which offered the best potential for preservation of function [ 72 ], even if this reduced survival [ 35 , 65 , 75 ]. Multiple studies reported that men saw post-treatment erectile dysfunction as the most important factor they overcame [ 34 , 54 , 56 , 89 ], with the shame of erectile dysfunction further compounded by incontinence disrupting their sexual relationships [ 55 , 62 , 80 ]. Decline in sexual function made men feel ‘not worthy’, less of, or unable to be a man compared to pre-treatment [ 30 , 31 , 33 , 66 , 77 , 90 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Retaining sexual function was also so important to some men that they recounted choosing treatment depending on which offered the best potential for preservation of function [ 72 ], even if this reduced survival [ 35 , 65 , 75 ]. Multiple studies reported that men saw post-treatment erectile dysfunction as the most important factor they overcame [ 34 , 54 , 56 , 89 ], with the shame of erectile dysfunction further compounded by incontinence disrupting their sexual relationships [ 55 , 62 , 80 ]. Decline in sexual function made men feel ‘not worthy’, less of, or unable to be a man compared to pre-treatment [ 30 , 31 , 33 , 66 , 77 , 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…Men described gaining ‘boobs’ [ 37 , 59 ], demonstrating how men immediately saw gynaecomastia as a signifier of their feminine transition. Many also attributed emotional changes to ADT—crying more often [ 53 , 80 ], becoming sentimental [ 59 ], and even wanting to bake more often [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Loss of self has been studied in the context of the patient with some evidence of the impact in cancer survivors [38] and chronically ill patients [39] and highly associated to self-esteem, but loss of self has rarely been examined in caregiver research. Extant studies have found loss of self mostly among caregivers that are spouses, younger, and women [23].…”
Section: Plos Onementioning
confidence: 99%